Accountability of The Government of The Republic of Indonesia For Illegal Migrant Workers - Amilatul Khoiriyah; Didiek Wahju Indarta (Warmadewa Press, 2024)
The accountability of the Indonesian government towards illegal migrant workers. This study examines how the government is accountable to illegal Indonesian migrant workers. This study aims to find out the causes, obstacles, and legal protection of illegal Indonesia migrant workers. This study uses a normative approach used to examine the protection of migrant workers in the context of government accountability for illegal migrant workers. The data sources used are primary data and secondary data and data analysis using qualitative descriptive analysis. The results of the study can be concluded that illegal Indonesian migrant workers do not receive strong legal protection and accountability from the government like legal migrant workers. This study recommends the need for stricter supervision of institutions that open service services to work abroad and for the public to be aware of false information about the rapid departure of Indonesia's migrant workers.